MODELING OF THE “IDRESM” ELECTRONIC JOURNAL PUBLICATION PORTAL USING THE WATERFALL MODEL - Ridwan Dwi Irawan; Muh Adha; Muhamad Paliya Sadana; Zitnaa Dhiaaul Kusnaa Washilatul Arba’ah; Ema Utami (Informatika, Universitas Jenderal Soedirman, 2022)
The utilization of various information technologies can increase the effectiveness and efficiency of the scientific publication process. Design can realize one of the uses of Information Technology in designing an electronic journal information system is that tools can use to solve these problems. The electronic journal information system is the collection, data collection, management, and or publication of scientific journals electronically. In addition, if the correct information can accompany the selection of journals, it will increase the effectiveness of publication activities in terms of time efficiency. Therefore, to support time management must be supported by a system design that includes journal subsystem information in planning the selection of open access journals when publishing. Based on the description above, this integration system aims to assist in compiling a journal integration system design based on software requirements analysis. In addition, the system development method used is the waterfall which consists of requirement analysis, system design, implementation, testing, deployment, dan operation & maintenante. The design uses a DBMS, UML, ERD, Wireframe, and database implementation.The results indicate that the system can assist in selecting journals that are following their fields to estimate open access journals based on the estimated submission time. In addition, the integrated approach that has been successfully implemented as a system has four subsystems: the primary database, human resource system, index system, and payment system.